DOGIELIUS LUCKNO WENSIS N. SP. (MONOGENEAN : DACTYLOGYRIDAE) IN SECURICULA BACAILA (HAM.) FROM LUCKNOW - AGRAWAL, NIRUPAMA; SHARMA, RICHA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
Dogielius lucknowensis n, sp. is described from Securiculabacaila Ham.), purchased from the local fish-market, Lucknow, It is characterised by the number of head organs, shape of accessOry piece of cirrus, structure of egg and number of marginal hooks.